Short-segment and intrasphincteric gastroesophageal reflux. Issue 4 (July 2016) - McColl, Kenneth E.L.; Derakhshan, Mohammad H.; Mitchell, David R.
Abstract : Purpose of review: The traditional gold standard for measuring gastroesophageal acid reflux has been by placing a pH sensor 5 cm proximal to the lower esophageal sphincter. It is known that damage induced by reflux is maximal near to the gastroesophageal junction and this has stimulated interest in determining acid reflux at that site. Recent findings: The extent of esophageal exposure from refluxing gastric acid is inversely related to the distance proximal to the gastroesophageal junction. In addition, the pH transition point from gastric to esophageal pH can be displaced proximally within the lower esophageal sphincter without complete loss of sphincter tone. This intrasphincteric reflux is associated with proximal extension of cardia mucosa because of columnar metaplasia of the most distal esophageal squamous mucosa. Summary: The most distal esophageal mucosa is exposed to substantially greater gastric acid refluxate than that recorded at the traditional site 5 cm proximal to the lower esophageal sphincter.